Fostering social inclusion through multilingual habitus in Estonia: a case study of the open school of Kalamaja and the Sakala Private School (online, 2017)
Abstract: After the restoration of independence in 1991, Estonia continued with a parallel school system with separate public schools operating for Russian- and Estonian-speaking children. Seen as a developmental
10.17645/si.v5i4.1149
Keywords: (thesoz)Estland; (thesoz)Demokratisierung; (thesoz)integrative Erziehung; (thesoz)Schule; (thesoz)Spracherwerb; (thesoz)Planung; (thesoz)Mehrsprachigkeit; (thesoz)Habitus; (thesoz)Inklusion; (thesoz)soziale Integration